TINJAUAN HUKUM KEADAAN MEMAKSA(FORCE MAJEURE) DALAM PELAKSANAAN KONTRAK BISNIS PADA MASA PANDEMI COVID-19 - Besty Habeahan; Sena Rusiana Siallagan (Magister Hukum Universitas HKBP Nommensen, 2021)
The Legal Review of Force Majeure in the implementation of business contracts during the covid-19 pandemic objectives of knowing whether covid 19 pandemic defined by the government as a national disaster which can be classified as a force majeure in the implementation of business contract and to find out how to solve the law against default in the implementation of business contract during the covid 19 as a national disaster. The library research, namely the research conducted in the library where the data is obtained from available data by reading and studying books such as laws of regulation, Scientific works, dictionaries and so on. Based on the method used, the result of this study indicate that force majeure is relative, so the cases that occur must be studied first, because not all the parties get loss but some of them get profit, for the implementation of achievement can be done by considering great effort and sacrifice. Relative Force Majeure is exemption from lost and interest costs, but not for cancelation of agreement. A right solution to solve from dispute is by negotiating with the parties, because the covid 19 pandemic it’s self is a new event.